Tomorrow's world : a look at the demographic and socio-economic structure of the world in 2032 - Laurent, Clinton R., 1948- (Wiley, 2013)
"Imagine the enormous advantage a corporate strategist or marketing professional in, say, 1990 would have had if they'd had access to a technology that permitted them to see, with a high degree of accuracy, the epic economic and social shifts that would occur over the next couple of decades. Imagine how they could have used their advance knowledge of the emergence of the massive Chinese middle class or the emergence of the global affluent consumer. Now imagine that you had such a fantastic instrument at your disposal. What kind of insights might it provide into how the world will develop over the next twenty years? What impact would that information have on your organisation's success? Tomorrow's World takes such speculation out of the realm of science fiction and into the real world. Written by the founder and Managing Director of Global Demographics Ltd., a top demographic agency that consults with companies worldwide on market and business planning, it maps out the world's near future as seen through the lens of demography. Must reading for business leaders, financial analysts, marketers, brand managers, government policymakers and economists, Tomorrow's World: Provides key demographic data for 74 countries, comprising 79% of the world's population and 92% of global GDP; Offers coverage of significant changes, over the next two decades, in population, households, labour force, household incomes, consumption, environment and other factors; Distills official census results and data from a range of major indices for all 74 nations down into demographic patterns across 7 major regions for easy analysis; Treats India and China (each of which comprises 20% of the world's population) as separate regions; Groups richer nations, including Hong Kong, Singapore, Japan, South Korea, Taiwan, Macau, Australia, and New Zealand, together as a discrete region; Treats poorer nations, such as Malaysia, Indonesia, Thailand, Philippines, Vietnam, Cambodia, Sri Lanka, Pakistan, and Bangladesh, as separate regions; Supplies you with a sounding board against which to test the veracity of your current assumptions and the fitness of your strategy and long-term business planning. Trying to steer your organisation into the future without all the facts in hand is like going into battle with an unloaded gun. Read Tomorrow's World and arm yourself with the information and analysis you need to form a clear picture of how our socio-economic landscape will evolve over the next two decades, target the most promising emerging business and investment opportunities and identify the most serious threats to your ongoing success."--